Formation and decomposition of methane hydrate in coal - Smirnov V. G. Vyacheslav Gennadjevich; Manakov A. Y. Andrey Yurjevich; Ukraintseva E. A. Elissa Alekseevna; Villevald G. V. Galina Vasiljevna; Karpova T. D. Tamara Dmitrievna; Dyrdin V. V. Valeriy Vasiljevich; Lyrshchikov S. Yu. Sergey Yurievich; Ismagilov Z. R. Zinfer; Terekhova I. S. Irina Sergeevna; Ogienko A. G. Andrey Gennadjevich (2016, 2016)
Title screen